ANALYSIS OF GEOLOGICAL STRUCTURE AND GEOMECHANICAL ON BASEMENT NATURAL FRACTURE OF KAYSAFA FIELD, JABUNG BLOCK, JAMBI SUB-BASIN- SOUTH SUMATRA - NOVIARDI YULIAN (NIM: 22015031), INDRA
The research area is located at Jabung block working area which is oil and gas producing field. In this field there is a reservoir potential that is found on the fracture of Late Eocene basement. In the research area the basement essentially structured in height position. The tectonic complexity that occurs as well as the weathering process makes the basement in this basin have a potential as hydrocarbon reservoirs. The reservoir characteristic is known by evaluating the wireline and image log to predict the reservoir potential on basement fracture. Geomechanical method is executed to know the present day of in-situ stress in the research area. The type of basement that occurs as hydrocarbon reservoir in the research field is granite fractured. The results of DST (Drill Steam Test) data on granite fractured recorded in Ibase-1 wells which flowed 1.9 MMSCFPD & 100 BCPD. From seismic data, the top of basement reservoir unit picked on the peak between the onlap sediments. The higher slopes of fractured granite which present in the study area have more possibility to accumulate the hydrocarbons. The main objective of the study was to be able to find out the characteristics of potential natural fracture basement reservoir by applying structural geological approaches using 3D seismic and geomechanical data. From the results of geomechanical analysis it is assumed that in-situ stress is also very influential in the fracture analysis of Slip Tendency (Ts), Dilation Tendency (Td) and Fracture Stability (Fs). Geomechanical analysis in the research area indicates the study area is controlled by a strike-slip fault rezime. Analysis of Slip Tendency (Ts), Dilation Tendency and Fracture Stability (Fs) in fault areas of Northeast-Western trending showed its has a tendency to reactivate based on geomechanical analysis result.